Effect of Fermented Kangkong Seed (Ipomoea reptans Poir.) on Characteristics and Histology of Female Quail Reproductive Organs - Astuti Kusumorini; Rachmat Wiradimadja; Ramadhani Eka Putra; Ana Rochana; Denny Rusmana (UIN Sunan Gunung Djati Bandung, 2021)
Quail has a high reproductive ability, which can reach 3 to 4 generations a year. The quail also have high eggs productivity and capable of producing 250-300 eggs/quail/year. Egg production is closely related to the reproductive system and feed. It is necessary to know the effect of feeding fermented kangkong on the characteristics and histology of the quail reproductive organs. The increase in livestock population should be balanced with an increase in the availability of feed. Kangkong seeds waste (Ipomoea reptans Poir.) is rejected seeds from seed factories that have the potential to become alternative feed ingredients because it contains about 13.46% protein. The purpose of this study was to determine the effect of fermented kangkong seed feed (Bikafer) on the characteristics of reproductive tract organs and histology of quail oviducts because feeds affect the development of the reproductive tract and quail egg production. This study used a completely randomized design method (CRD) with 5 treatments and 4 replications. The treatments were as follows: R0 = commercial feed, R1 = 0% (Bikafer), R2 = 7.5% (Bikafer), R3 = 15% (Bikafer) ,R4 = 22.5% (Bikafer). Data were analyzed using one-way ANOVA with a significance level of 95% (α = 0.05) and the Kruskal-Wallis test, while histological observations were described descriptively. The results showed that there were significant differences in the characteristics of the uterus, vaginal length, and isthmus weights. The histology of the quail reproductive tract developed well and showed the tunica mucosal tissue, serous tunica, muscular tunica, goblet cells, epithelium, and tubular gland cells.